Numerical Investigation of Heat and Mass Transfer through the Preheater System in CementManufacturing Plant - Alwan Saleh, Fouad; Kadhim Hussein, Ahmed (Journal of Engineering and Sustainable Development, 2006)
In this study, the last part of the preheater system in a cement manufacturing plant which is called pyroclon system is studied. The study covers the amount of tertiary air from cooler and its temperature effect on temperature of calcination also its effect on the amount of fuel that is supplied to pyroclon. Also, the study of the amount of hot gases from rotary kiln and its temperature effect on the temperature of calcination, and on the amount of supplied fuel. The results of the present work explained also the effect of quantity of the raw meal that enter the pyroclon and its temperature effect on the temperature of calcination and the amount of supplied fuel .Heat balance for pyroclon system and mass balance for all preheater systems and its chemical reactions are included. Then a computer program is constructed in order to calculate temperature distribution for gases and particles along pyroclon by considering the amount of the heat lost, which is transferred from the gas to particle and from the particle to the wall, also from the gas to the wall, depending on conduction, convection and radiation in order to find the exit temperatures of gas and particles from pyroclon and to find the range of the pyroclon working for different values of gas velocities and the amount of fuel supplied.